1985
DOI: 10.1093/cvr/19.4.181
|View full text |Cite
|
Sign up to set email alerts
|

Experimental models of heart failure

Abstract: Experimental models of heart failure can be used to address specific questions not easily answered in patients, but no single model can reproduce exactly any of the clinical syndromes of heart failure since these are dominated by fatigue and breathlessness. Heart failure may be induced experimentally by pressure loading, volume loading, myocardial infarction, or by the creation of other disease states within the myocardium. Pressure loading may be especially useful in the study of ventricular hypertrophy, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…In the groups of NTGϩADR and CYP2E1-silence ϩADR, ADR was induced by intraperitoneal injection in a constant volume of saline at 4 mg/kg every other day for a total of 2 weeks. 31 The groups of NTGϩsaline and CYP2E1-silenceϩsaline mice received the same amount of saline. Echocardiography was performed on all of the mice at day 0 (the day before the treatment of ADR).…”
Section: Adriamycin Treatmentmentioning
confidence: 99%
“…In the groups of NTGϩADR and CYP2E1-silence ϩADR, ADR was induced by intraperitoneal injection in a constant volume of saline at 4 mg/kg every other day for a total of 2 weeks. 31 The groups of NTGϩsaline and CYP2E1-silenceϩsaline mice received the same amount of saline. Echocardiography was performed on all of the mice at day 0 (the day before the treatment of ADR).…”
Section: Adriamycin Treatmentmentioning
confidence: 99%
“…12) Either intravenous or intraperitoneal injection or coronary artery local injection can be adopted; 13) (2) Overdrive-pacing; 14) (3) Viral infection; 15) (4) Furazolidone induction; (5) High salt diet in order to raise blood pressure, cardiac preload and afterload, which contribute to heart enlargement and heart failure. 16,17) In this article, rats models of chronic congestive heart failure were established by intraperitoneal injection, and it was identified that rats possess cardiomyopathy and chronic congestive heart failure properties through the index of pathological and hemodynamic detection.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of ischaemic tissue and the resulting heart failure is determined by the position of the ligation and the degree of coronary collateral circulation (Smith & Nuttall 1985, Elsner & Riegger 1995. The disadvantages of this method are the necessity to perform a thoracotomy, an initial high mortality rate, mostly caused by arrhythmia, and the development of mild or moderate heart failure during long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…19861. Nevertheless it has rarely been used in experimental haemodynamic investigation of surgical therapeutic approaches to the management of cardiac failure such as dynamic cardiomyoplasty, mechanical assist devices or artificial hearts. Apart from the induction of myocardial infarction due to coronary ligation no other model of acute heart failure in pigs is reported in the literature (Smith & Nuttall 1985, Elsner & Riegger 1995.…”
mentioning
confidence: 99%